How Safe Is the Use of Ultrasound in Prenatal Medicine? Facts and Contradictions. Part 1 – Ultrasound-Induced Bioeffects - Dudwiesus, Heiko; Merz, Eberhard (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
The “Ordinance on Protection Against the Harmful Effects of Non-Ionizing Radiation in Human Applications” will go into effect at the beginning of 2021 1. § 10 of this ordinance prohibits non-medical fetal ultrasound exposure thereby resulting in uncertainty, particularly among affected patients, with respect to the generally accepted theory regarding the lack of ultrasound side effects. Although not a single study has shown a detrimental effect on fetal or child development following exposure to ultrasound, the Federal Ministry for the Environment, Nature Conservation and Nuclear Safety has justified the ban with the purely hypothetical possibility of an unidentified side effect. The first part of the following study shows which ultrasound-induced biophysical effects are known and which dose-dependent threshold values must be taken into consideration. In particular, the study focuses on the well-researched heat effect with some in vivo measurements in humans showing that the actual temperature increase is less than the theoretically calculated values. The planned second part of this study will discuss the non-thermal effects and present the most important epidemiological studies.Mit dem Jahreswechsel 2020/2021 wird die „Verordnung zum Schutz vor schädlichen Wirkungen nichtionisierender Strahlung bei der Anwendung am Menschen (NiSV)“ in Kraft treten 1. Da diese Verordnung mit seinem § 10 auch die nichtmedizinische Ultraschallexposition des Fötus unter Strafe stellt, ist insbesondere unter den betroffenen Patientinnen eine Unsicherheit in Bezug auf die allgemein postulierte Nebenwirkungsfreiheit von Ultraschall aufgetreten. Obwohl keine einzige Studie einen schädlichen Einfluss auf die fetale und kindliche Entwicklung nach Ultraschallexposition erkennen lässt, begründet das BMU das Verbot mit der rein hypothetischen Möglichkeit einer bislang nicht erkannten Nebenwirkung. Die nachfolgende Arbeit zeigt im ersten Teil, welche ultraschallinduzierten biophysikalischen Effekte bekannt und welche dosisabhängigen Schwellenwerte zu beachten sind. Dabei steht insbesondere die gut erforschte Wärmewirkung im Mittelpunkt, wobei einige in vivo erfolgten Messungen am Menschen zeigen, dass die tatsächliche Temperaturerhöhung hinter den theoretisch errechneten Werten zurückblieb. Im geplanten zweiten Teil werden die nichtthermischen Wirkungen behandelt sowie die wichtigsten epidemiologischen Studien vorgestellt.